2019
DOI: 10.3390/ijerph16204051
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Physical Activity Level and Depression of Elderly People Living Alone

Abstract: Background and objectives: Only a few studies analyzed the physical activity level of elderly people living alone in local communities and evaluated the relationship between it and mental health. The purpose of this study was to investigate the relationship between regular physical activity and depression in the elderly living alone and to provide basic data for the prevention of depression in the elderly. Materials and Methods: We analyzed 256 elderly people living alone aged 65 years or older who completed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 21 publications
3
44
0
2
Order By: Relevance
“…The results are in line with other studies indicating that PA confers considerable protection against chronic diseases (diabetes, hypertension and hypercholesterolaemia) as well as mental health problems such as anxiety and depression [3,4,20,21,46]. The practice of PA helps prevent depression where it is stated that performing flexibility exercises could reduce the risk of depression by up to 81% [47]. These results are in line with those obtained in the present study where an inverse relationship between PA and depression can be observed.…”
Section: Discussionsupporting
confidence: 93%
“…The results are in line with other studies indicating that PA confers considerable protection against chronic diseases (diabetes, hypertension and hypercholesterolaemia) as well as mental health problems such as anxiety and depression [3,4,20,21,46]. The practice of PA helps prevent depression where it is stated that performing flexibility exercises could reduce the risk of depression by up to 81% [47]. These results are in line with those obtained in the present study where an inverse relationship between PA and depression can be observed.…”
Section: Discussionsupporting
confidence: 93%
“…Among the 27 studies included, 14 included elder populations of 65 years or over [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 39 , 42 , 44 , 45 , 51 , 54 ]. However, only 2 studies [ 17 , 40 ] included as covariates the interaction between age groups and PA to facilitate the comparison across age groups of PA on MH.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, sedentary older adult report significantly higher levels of anxiety and depression and reduced quality of life when compared to physically active individuals (de Oliveira et al., 2019). This holds for various intensities of physical activity, as, for example, Yoga interventions (Noradechanunt et al., 2017), flexibility exercise (Byeon, 2019) or marathon sports (Batmyagmar et al., 2019). There are several hypotheses regarding the pathogenesis of depression, including the monoamine hypothesis, the vascular depression hypothesis, and the cytokine hypothesis (Khalaf et al., 2015; Marathe et al., 2018).…”
Section: Introductionmentioning
confidence: 99%